PENGARUH BRAND IMAGE, KUALITAS PRODUK, DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN MOTOR HONDA (STUDI PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS MERCU BUANA YOGYAKARTA) - Awaludin Awaludin; Hamzah Gunawan (POLITEKNIK LP3I JAKARTA, 2024)
This study aims to examine the influence of brand image, product quality and electronic word of mouth on Honda motorcycle purchase decisions (Study on Students of the Faculty of Economics, Mercu Buana University, Yogyakarta). The independent variables in this study consisted of Brand Image, Product Quality, and Electronic Word Of Mouth. While the dependent variable is Purchase Decision. This study used a quantitative approach. The population in this study is students of the faculty of economics, Mercu Buana University, Yogyakarta. Sampling using proportionate stratified random sampling method. There were 96 student samples. Data analysis techniques use multiple regression analysis, classical assumption tests and hypothesis tests with SPSS 25. The results of this study are partially brand image, product quality and electronic word of mouth have a positive and significant effect on purchasing decisions. Simultaneously, brand image, product quality and electronic word of mouth have a positive and significant influence on purchasing decisions. Key words: Brand Image, Product Quality, Electronic Word Of Mouth, Purchasing Decision.